Creation as Sacrament: An Orthodox Contribution to the Cultivation of an Ecological Ethos - Coman, Viorel ca. 20./21. Jh. (Communio viatorum, 2024)
This article looks at the contribution of Dumitru Stăniloae’s theology of the sacramentality of creation for the cultivation of an ecological sensitivity, attending in particular to his ideas that the entire created reality is God’s gift to humanity and that the cosmos has a mysterious or apophatic dimension. This helps in developing a Christian ecology whose central idea is of non-possession or non-domestication of the world by human beings. Understanding the world thus is seen as world-aﬃrming and a reminder that creation cannot be treated as mere utility, property, or raw material, but is always also a vehicle of grace and spiritualization.